Rationality of Use of Antibiotic at North Region City Primary Health Care Centre in Kediri City - Hanie Kusuma Wardani; Krisogonus Ephrino Seran; Yogi Bhakti Marhenta; Febriarmayenri (Universitas STRADA Indonesia, 2022)
The implementation of health services by ensuring safety, effectiveness, and affordable costs for people who receive treatment is one of the efforts carried out by the Rational Drug Use program. It is said that the use of drugs is rational if the patient gets treatment according to clinical needs, the dose is as needed, the drug can be used for a sufficient period of time and at an affordable cost. This study aims to determine the rationality of the use of antibiotic drugs at North Region City Primary Health Care Centre in Kediri City with the indicators of Right Indication, Right Patient, Right Drug, Right Dosage, and Beware of Drug Side Effects. This study is a descriptive study with retrospective data collection by looking at prescriptions and medical records of patients using antibiotics and supported by open interviews with pharmacists. Based on the results of the study showed that the use of antibiotics in 273 samples obtained Penicillin class antibiotics was 46.89%, Other Antibiotics of 26.01%, Antituberculosis of 8.42%, Quinolones at 11.72%, Aminoglycosides of 5.13%, Tetracyclines of 1.10%, and Macrolides of 0.73%. The percentage of rationality for the use of antibiotic drugs which includes indicators of Right Indication, Right Patient, Right Drug, Right Dosage, and Alert for Drug Side Effects is 96%.